Synopsis of the genus Axiniphyllum (Asteraceae, Millerieae) endemic to Mexico - González-Zamora, Alberto; Villaseñor, José Luis (Instituto de Ecología, A.C., 2017)
Background and Aims: The genus Axiniphyllum is endemic to Mexico, distributed in the southern and western part of the country. Its members are characterized by its perennial herbaceous habit, opposite and lobulated leaves, basally connate, and 4-angulate cypselae lacking a pappus. The objective of this research was to perform a synopsis of the genus, including descriptions, a key for species identification, and a distribution map.Methods: Specimens of Axiniphyllum deposited in different Mexican herbaria were reviewed. Identification was carried out using taxonomic treatments and revision of type specimens.Key results: Species of Axiniphyllum can be recognized by the morphological variability of the leaves and the heads; A. pinnatisectum and A. sagittalobum display ligulated flowers. Description of each species was increased with respect to what has been previously reported in the literature due to the addition of new observations.Conclusions: Five species are recognized in Axiniphyllum; all species can be considered as rare because the scarcity of their collections. Some localities where they have been recorded are currently strongly affected by human activities.